1995
DOI: 10.1164/ajrccm.152.4.7551376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for pulmonary barotrauma: a multivariate analysis.

Abstract: Previous investigations have suggested that elevated airway pressures increase the risk of ventilator-induced pneumothorax. However, risk factor analysis using multivariate techniques has not been done. We investigated the hypothesis that airway pressures would not independently correlate with pneumothorax when underlying disease was considered. All ventilated patients over a 1 yr period in the Hohenburg Critical Care Unit at the University of Alabama were followed until death or discharge from the ICU. Ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 10 publications
3
60
1
6
Order By: Relevance
“…Although one study showed that the incidence of pneumothorax decreased after implementation of protective lung strategies [27] , several recent studies comparing low tidal volume with conventional ventilation in ARDS failed to demonstrate any reduction in barotrauma when low tidal volumes were used [41][42][43] . Previous literature showed the incidence of barotrauma did not relate to the ventilatory settings [22,31,41,44] but a low compliance was associated with a high incidence of barotrauma, which suggested that barotrauma has been more related to the underlying process than the ventilatory setting [40] .…”
Section: Factors For Prmvmentioning
confidence: 95%
See 1 more Smart Citation
“…Although one study showed that the incidence of pneumothorax decreased after implementation of protective lung strategies [27] , several recent studies comparing low tidal volume with conventional ventilation in ARDS failed to demonstrate any reduction in barotrauma when low tidal volumes were used [41][42][43] . Previous literature showed the incidence of barotrauma did not relate to the ventilatory settings [22,31,41,44] but a low compliance was associated with a high incidence of barotrauma, which suggested that barotrauma has been more related to the underlying process than the ventilatory setting [40] .…”
Section: Factors For Prmvmentioning
confidence: 95%
“…That is why these patients are at risk of pneumothorax [30] . PRMV is most closely correlated with ARDS [31] , a heterogeneous disease in which the lung is physiologically small and with low compliance [32] . The dependent lung regions tend to be collapsed and the lung regions subject to high pressure overinflation and alveolar rupture are nondependent regions when positive end-expiratory pressure (PEEP) inflates and recruits some of collapsed regions during mechanical ventilation [33,34] .…”
Section: Disease Associated With Pneumothoraxmentioning
confidence: 99%
“…ср. у больных с ОПЛ/ОРДС [2,11,12,21]. В настоящее время так же продолжаются дебаты о гипоксемии, как предикторе летальнос ти больных с ОРДС и ПОН [3,14,19].…”
Section: таблицаunclassified
“…Так, у больных с тяжелы ми нарушениями газообмена в легких и крайне низкой торакопульмональной податливостью, да леко не всегда удается снизить пиковое давление до безопасного уровня и избежать развития ги перкапнии, что особенно актуально у больных с внутричерепной гипертензией, кардиальной па тологией, метаболическим ацидозом и т. д. Кроме того, ограничение ДО у данного контингента больных приводит к коллабированию альвеол, Острая двусторонняя бактериальная пневмония 1 1 1 1 2 1 Аспирационный пневмонит 2 3 1 1 --Двусторонняя нозокомиальная пневмония 2 -2 2 2 2 ИТОГО 17 9 17 11 12 8 ухудшению газообмена в легких и является при чиной развития ателектотравмы [2,8,11,12]. Есть сообщения об эффективности применения больших дыхательных объемов, маневра откры тия легких, периодического перераздувания лег ких, а так же о необходимости дифференцирован ного выбора параметров ИВЛ в разные стадии острого повреждения легких, и при различных формах ОРДС [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Этим обусловлено продол жение интенсивного изучения способов оптими зации параметров респираторного паттерна у больных с ОРДС.…”
unclassified
“…Froese A. et al было показано, что при самостоятельном дыхании происходит вентиляция наиболее перфузируемых участков легких, тогда как дыхательный объем при проведении ИВЛ распределяется в зонах со снижен ным кровотоком. Сохранение самостоятельного ды хания во время ИВЛ приводит к значительному улучшению вентиляционно перфузионных отноше ний по сравнению с тотальной респираторной под держкой, что является результатом перераспределе ния дыхательного объема в хорошо перфузируемых участках легкого [10]. Даже обеспечение 10% венти ляции самостоятельным дыханием заметно улучша ет вентиляционно перфузионные отношения в лег ких, увеличивает сердечный индекс, РаО 2 , транспорт кислорода, что согласуется с полученными нами ре зультатами [11].…”
Section: динамика физиологических показателей у больных с оппл (м±σunclassified